PROSES MANAJEMEN KINERJA PEGAWAI IAIN RADEN INTAN LAMPUNG - Jauhari, Tontowi (BINA' AL-UMMAH, 2014)
Organizational effectiveness will be achieved with the clarity of mission , strategies , and objectives of the organization, and it is as well, road or means to build performance of organization. Performance management is a continuous system in creating clear working relationship between persons and organizations.In order to achieve the organization goal, and to build the good communication atmosphere in organization, it is necessary to construct measures of performance of management process ; performance planning , implementation performance, feedback , Riview performance , performance measurement , performance evaluation. Effective process of performance management could make changes for individuals ,organizations, and of creating new culture in an organization.